Damage analysis on furnace radiant tube using energy dispersive X-ray analysis - Mohd, Harun; Mahdi Ezwan, Mahmoud; Zaifol, Shamsu; Norasiah, Kasim; Zaiton, Selamat; Katrul Hisham, Alauddin; Zulkifli, Zainon (Universiti Malaysia Perlis, 2010)
International Conference on X-Rays and Related Techniques in Research and Industry (ICXRI 2010) jointly organized by Universiti Malaysia Perlis (UniMAP) and X-Ray Application Malaysia Society (XAPP), 9th - 10th June 2010 at Aseania Resort Langkawi, Malaysia.